PENGARUH MODEL PROBLEM-BASED LEARNING (PBL) DISERTAI MEDIA TIGA DIMENSI TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN FISIKA DI SMA NEGERI 4 JEMBER - Ayu Fajarotul Maghfiroh; Albertus Djoko Lesmono; Bambang Supriadi (FKIP Universitas Jember, 2017)
The aim of this research is to study the influence of problem-based learning model with the three dimension media through the creativity of student’s thought ability and the student result in learning physics. The creativity, in this case, the ability to have a creative idea is needed to have an ability in problem solving and the student result in learning physics. However, in fact, the creativity of student’s thought ability is not complete maximal enough this research is experiment research. It conducted in SMAN 4 Jember. The data are collected by test, portofolio, observation, interview, and documentation. To examine the hypothesis, this research used independent sample t-test with SPSS 16 version. According to independent sample t-test analysis in the creativity of student’s thought, show that H0 is rejected, it mean that the creativity of student’s thought of experiment class is different with control class. The result of independent sample t-test analysis in the student result show that H0 is rejected, it mean that the student result of experiment class is different with control class. In conclussion, the problem-based learning model with three dimension media has an significance influential to the creativity of student’s thought ability and the student result in SMAN 4 Jember.